Study of Political Representations: Diplomatic: A Study of Martyr Bhagat Singh's Political Representations and Multiple Personalities (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Martyr Bhagat Singh has a very brief period of activepolitical life. In this brief time span he has transcended to the top of athought process which make him ever relevant to the immerging situations. Asthese years there is increased interest in him by the common man so there is anurge to have more thorough understanding. The short period of active life also creates a paradox.In absence of thorough understanding of the process of his revolutionarygrowth, the scope for interpretation of shahid for narrow benefit has been onrise. Thus there is an urgent need to have better understanding of the growthof thought process. Great men of all generations have been anxious aboutimprovement of the lot of human beings. But how to realize it remains aformidable task for e very age. Even though the goal is similar, the means toachieve the goal can differ. And this difference in approach can generate a lotof controversy. This is precisely what happened between Mahatma Gandhi andSardar Bhagat Singh, the two great statesmen of modern India. As a result,Bhagat Singh has been ranked as a rival of Mahatma Gandhi. It has been held insome quarters that while Gandhi was the sun of nationalism around which all theplanets of the Indian National Congress revolved, Bhagat Singh was a star thatpursued an orbit of its own. What would be better to call Bhagat Singh a poet,historian, writer, philosopher, artist, poet, communist, socialist, Marxist orat the most a family man? A close study of Singh’s character and nature alongwith his letters throws light on his various shades. Yet, still, alwaysconfusion arises. What would be better to call him? Politician, states man,nationalist, national builder, patriot, freedom fighter, terrorist,revolutionary, administrator; list may be long. However, question here is whichrole was dominant in his life? Hence, in this paper an attempt is made to tracehim as a man of multiple personalities. Another attempt is made to trace thefavorable factors that nourished his growth as freedom fighter.